The correlation between plasma malondialdehyde levels and pain in adolescent females diagnosed with primary dysmenorrhea - Ocktariyana Ocktariyana; Dian Lestari; Abdul Kadir; Listrianah Listrianah; Handayani Handayani (Indonesian Society for Biochemistry and Molecular Biology, 2023)
Background: Endometrial inflammation factors play a crucial role in the common pathophysiology of primary dysmenorrhea. Malondialdehyde (MDA), a byproduct of inflammatory processes, might be correlated with primary dysmenorrhea in adolescents. Objective: To assess plasma MDA levels in patients with primary dysmenorrhea. Methods: This cross-sectional study involved the collection of blood samples from 23 teenage females with primary dysmenorrhea and 23 age-matched individuals without this condition. Plasma MDA levels were quantified through spectrophotometry. The independent t-test was employed to ascertain the disparity in plasma MDA levels between the two groups, while the Pearson correlation test was utilized to analyze the relationship between pain severity and oxidative stress levels. Results: Plasma MDA levels were significantly higher in females with primary dysmenorrhea than in the control group (0.631 ± 0.105 and 0.395 ± 0.076, respectively). A significant difference in oxidative stress levels was observed between the case and control groups (p<0.001). Furthermore, a robust positive correlation was observed between plasma MDA levels and pain severity in adolescent females with dysmenorrhea (r2 = 0.564, p<0.001). Conclusion: The plasma MDA is increased in adolescent females with primary dysmenorrhea.